1997
DOI: 10.2527/1997.7551409x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value of pearl millet for lactating and growing goats.

Abstract: Studies were conducted to assess nutritional value of pearl millet grain (Pennisetum glaucum [L] R. Br.) for lactating and growing goats. Three complete diets containing either 40% corn, 40% pearl millet, or 40% corn and pearl millet mixed 1:1 (wt/wt) were balanced to contain 16% crude protein and 2.24 Mcal DE/kg on an air-dry basis. Forty-five does were blocked by kidding date and randomly assigned to diets for a 7-wk investigation. Feed intake and milk production were unaffected (P > .25) by treatment, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0
13

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 13 publications
5
7
0
13
Order By: Relevance
“…Moreover, the similar variation in the digestibility coefficients between diets based on corn or pearl millet was consistent with the results obtained by Gonçalves et al (2010). However, the similarity in the digestibility coefficients of diets in which corn grain was replaced by pearl millet grain is not unanimous in the literature, as some authors (Gelaye et al, 1997) reported a reduced digestibility following the inclusion of pearl millet grain in the diet attributed to the higher lignin content of this grain than corn grain. The inclusion of BMB in diets for feedlot cattle may result in increased feeding time due to the reduction of the energy content of diets, as reported by Cruz et al (2012) and Castro et al (2009).…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, the similar variation in the digestibility coefficients between diets based on corn or pearl millet was consistent with the results obtained by Gonçalves et al (2010). However, the similarity in the digestibility coefficients of diets in which corn grain was replaced by pearl millet grain is not unanimous in the literature, as some authors (Gelaye et al, 1997) reported a reduced digestibility following the inclusion of pearl millet grain in the diet attributed to the higher lignin content of this grain than corn grain. The inclusion of BMB in diets for feedlot cattle may result in increased feeding time due to the reduction of the energy content of diets, as reported by Cruz et al (2012) and Castro et al (2009).…”
Section: Discussionsupporting
confidence: 78%
“…Our CP values were in good agreement with the values reported by Haydon and Hobbs (1991) and Gelaye et al (1997). Burton et al (1972) found that CP content of pearl millet ranged between 88 and 209 g kg…”
Section: Protein Compositionsupporting
confidence: 82%
“…Phosphorus was the most abundant mineral in all cultivars followed by Mg and K, respectively. Similar mineral profiles for pearl millet were reported by Glew et al (1997) and Gelaye et al (1997). However, Oshodi et al (1999) found K to be the most abundant mineral in pearl millet followed by Mg. Levels of Mg and K were higher and lower, respectively, in our study than reported elsewhere (Sarena-Saldivar and Rooney 1995).…”
Section: Mineral Compositionsupporting
confidence: 58%
See 2 more Smart Citations